Digital Movement of Opinion Mobilization: SNA Study on #Dirumahaja Vs. #Pakaimasker - Edy Prihantoro; Fajar Rizali Rakhman; Rizky Wulan Ramadhani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
This study examines the role of #PakaiMasker and #DirumahAja hashtags on Twitter on shaping the mobilization of digital opinion support, measuring the effectiveness of the comparison of a network, actors between hashtags, and digital opinions. The theory used was Digital Movement of Opinion by looking at the level of actors and systems. The method used in this research is a mixture combining quantitative and qualitative methods. Quantitatively, this research looks at the communication networks from the sample of 2,000 tweet data: 1000 tweet data #PakaiMasker with 259 actors and 334 and 1000 tweet data #DirumahAja with 359 actors and 283 relationships using netlytic and gephi. Meanwhile, qualitatively, the researchers analyzed text that described and explained social networks. The results showed #DirumahAja was more able creating mobilization compared to #PakaiMasker. The success of the #DirumahAja was due to its extensive network system that able to reach actors using Twitter in giving their opinions regarding health campaigns during Covid-19 pandemic.